Hardy-Littlewood maximal operator on the associate space of a Banach function space - Karlovich, Alexei Yu (2022)
info:eu-repo/grantAgreement/FCT/5876/147204/PT This work was partially supported by the Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through the project UID/MAT/00297/2013 (Centro de Matemática e Aplicações).